Ecological Resilience Through Green Infrastructure: Analyzing the Role of Private Green Open Spaces in Tropical Megacities - Saskia, Cut Sannas; Winandari, Maria Immaculata Ririk; Wijayanto, Punto; Inavonna, Inavonna; Fatmawati, Teungku Nelly; Aziiz, Akhlish Diinal; Ischak, Mohammad; Tjiook, Wiwi (Infomatek, 2025)
Green open space is decreasing along with urban development. Development in urban areas has an impact on reducing green land which is important for urban resilience. In Jakarta, the reduction in water-absorbing surfaces has exacerbated environmental problems such as flooding, rising temperatures and decreasing biodiversity. This study aims to evaluate the ecological performance of green open spaces, especially in private homes in the Menteng area, Jakarta, which is recognized as the first garden city in Indonesia, as a representation for understanding the role of green open spaces in advancing urban sustainability and climate resilience. The focus is on the extent of private green open space that still exists in the city area, especially Menteng. Using mixed-method spatial analysis with GIS-based mapping and field surveys of more than 85 residential lots, this study applies the Basic Green Coefficient to measure green space coverage. The results show an average coefficient of 44%, indicating substantial integration of green spaces in the built environment. These private green areas increase rainwater infiltration, reduce flooding, reduce the heat island effect, regulate microclimate, and support air purification, carbon sequestration and biodiversity. Despite developmental pressures, Menteng’s environmentally friendly infrastructure continues to provide ecological functions that are in line with sustainability goals. This study aims to offer insights into improving urban ecology through green infrastructure, specifically green open spaces, and its role in strengthening urban sustainability, livability, and public health.